Ce- and manganese-doped aluminosilicate fluorescent materials and preparation methods and applications thereof

By doping cerium and manganese in fluorescent materials and adjusting their chemical composition and excitation conditions, multiple anti-counterfeiting and information encryption applications of fluorescent materials are achieved, solving the limitations of existing materials in excitation wavelength coverage and fluorescent color adjustment.

CN117327489BInactive Publication Date: 2025-03-25FOSHAN UNIVERSITY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311247916.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-25
Publication Date
2025-03-25
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing fluorescent anti-counterfeiting materials have limitations in excitation wavelength coverage and fluorescence color adjustment, and it is difficult to meet the needs of multiple anti-counterfeiting and information encryption.

Method used

A fluorescent material based on cerium and manganese doped aluminosilicates is used, and its chemical composition is Mg3-x-yCexMnyAl3+xSi4-xPO18. By adjusting the doping concentration and excitation wavelength of Ce3+ and Mn2+, the fluorescence color adjustment and a wide excitation emission wavelength range are achieved.

Benefits of technology

It realizes the rich fluorescent color performance of fluorescent materials at different doping concentrations, excitation wavelengths and temperatures, and improves the effects of multiple anti-counterfeiting and optical temperature measurement applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117327489B_ABST
    Figure CN117327489B_ABST
Patent Text Reader

Abstract

The present invention relates to a cerium- and manganese-doped aluminosilicate fluorescent material and its preparation method and application. The chemical composition formula of the fluorescent material is: Mg 3‑x‑y Ce x Mn y Al 3+x Si 4‑x PO 18 , where x is Ce 3+ The doping concentration of Mn is 0.02≤x≤0.04, and y is Mn 2+ The doping concentration of the fluorescent material has a value range of 0.03≤y≤0.17, the excitation wavelength range of the fluorescent material is 250-500nm, which is a band absorption, and the emission wavelength range is 317-750nm, which is a band emission. The fluorescent material has fluorescence characteristics such as a wide excitation and emission wavelength range, a strong fluorescence intensity, an adjustable fluorescence color and a better temperature response, and can be applied to optical temperature measurement and multiple anti-counterfeiting fields.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fluorescent materials, and in particular to a cerium- and manganese-doped aluminosilicate fluorescent material and a preparation method and application thereof. Background Art

[0002] Traditional anti-counterfeiting technologies include laser anti-counterfeiting, fluorescent anti-counterfeiting, magnetic anti-counterfeiting, temperature change anti-counterfeiting, etc. These anti-counterfeiting technologies generally have defects such as low technical content and easy deciphering of structural combinations. Fluorescent anti-counterfeiting technology has the advantages of wide coverage of excitation wavelengths, no background fluorescence, high physical stability and chemical stability, and has broad application prospects in the field of packaging anti-counterfeiting.

[0003] Fluorescent anti-counterfeiting materials are the core foundation of fluorescent anti-counterfeiting technology. Under the irradiation of ultraviolet light or infrared light, fluorescent anti-counterfeiting materials can quickly release energy after absorbing a certain amount of energy, presenting a bright and colorful fluorescent effect. They have been widely used in infrared anti-counterfeiting inks (green or red light under 780-1060nm infrared light), anti-counterfeiting printing inks (colorless under sunlight, red fluorescence under ultraviolet light) and anti-counterfeiting fibers with fingerprint characteristics.

[0004] In my country, the market capacity of the anti-counterfeiting industry can reach hundreds of billions of yuan. Multiple anti-counterfeiting and information encryption have become a development industry with broad application prospects in the 21st century. At present, the most common fluorescent anti-counterfeiting materials are mostly Tb 3+ , Yb 3+ and Er 3+ etc. are activated ions, based on Ce 3+ and Mn 2+ The fluorescent anti-counterfeiting materials and anti-counterfeiting technologies need to be explored. For example, patent document CN100482751C discloses a multi-color ratio high-efficiency luminescent anti-counterfeiting ink that can carry a password, which is composed of ytterbium fluoride as a sensitizing center compound, and at least one of the fluorides of erbium, neodymium, samarium, thulium and holmium as a luminescent center compound, and at least one of zinc fluoride, zirconium fluoride, germanium oxide, strontium fluoride, magnesium fluoride, sodium fluoride, zinc sulfide, ammonium fluoroaluminate, barium fluoride, cadmium fluoride, lanthanum fluoride, zinc oxide, boron oxide and zinc chloride as a luminescent center structure carrier to form a composition, after the composition is mixed and mechanically ground, a ceramic semi-finished product is obtained according to a precision firing procedure, and then the ceramic semi-finished product is ground into a powder product, and a certain amount of the product is taken as an anti-counterfeiting mother material and added to the ink. Summary of the invention

[0005] Based on this, in order to solve at least one technical problem existing in the prior art, the present invention proposes a cerium- and manganese-doped aluminosilicate fluorescent material and a preparation method and application thereof.

[0006] A cerium- and manganese-doped aluminosilicate fluorescent material, the chemical composition formula of the fluorescent material is: Mg 3-x- y Ce x Mn y Al 3+x Si 4-x PO 18 , where x is Ce 3+ The doping concentration of Mn is 0.02≤x≤0.04, and y is Mn 2+ The doping concentration has a numerical range of 0.03≤y≤0.17, the excitation wavelength range of the fluorescent material is 250-500nm, which is a band absorption, and the emission wavelength range is 317-750nm, which is a band emission, with a wider excitation wavelength and emission wavelength range.

[0007] Preferably, the fluorescent material has the characteristics of adjustable fluorescent color under different doping concentrations, excitation wavelengths and temperatures, specifically:

[0008] When the x value is fixed and the y value changes from large to small, the fluorescent color of the fluorescent material changes from orange-red to sky blue;

[0009] When the values ​​of x and y are constant, the excitation wavelength is changed, and the fluorescent color of the fluorescent material changes within the range of sky blue, emerald green and orange-red;

[0010] When the values ​​of x and y and the excitation wavelength are fixed, as the temperature changes from low to high from normal temperature, the adjustable fluorescence color range of the fluorescent material is from orange-red to sky blue.

[0011] Further preferably, when x=0.03, and the value of y changes from large to small, the fluorescent color of the fluorescent material changes from orange-red to sky blue;

[0012] When x=0.03, y=0.03, and the excitation wavelengths are 254, 320, 417, and 427 nm, respectively, the fluorescent colors of the fluorescent material are rose red, orange red, emerald green, and yellow, respectively;

[0013] When x=0.03, 0.03≤y≤0.17 and is a constant value, and the excitation wavelength is 300-330nm and is a constant value, within the range of 50-200°C, as the temperature changes from low to high, the adjustable fluorescence color range of the fluorescent material is from orange-red to sky blue. In this range, Ce 3+ and Mn 2+ Ions can achieve better co-excitation and better Ce 3+ and Mn 2+ ion fluorescence intensity ratio and larger fluorescence color changes.

[0014] More preferably, x=0.03, y=0.07, and the chemical composition formula of the fluorescent material is Mg 2.9 Ce 0.03 Mn 0.07 Al 3.03 Si 3.97 PO 18 , Ce of the material 3+ and Mn 2+ The fluorescence not only has a suitable fluorescence intensity ratio, but also shows a good temperature response. In the process of optical temperature measurement, 310nm light excitation is used, and Mn 2+ About Ce 3+ The fluorescence intensity ratio can sensitively respond to changes in temperature. At the same time, the change in fluorescence color in response to temperature is more obvious.

[0015] The fluorescent material of the present invention is Mg3Al3Si4PO 18 The matrix contains crystallographic Mg 2+ The grid can be Ce 3+ and Mn 2+ Ion occupation. Ce 3+ Ion fluorescence belongs to 5d-4f transition, which has the characteristics of nanosecond radiation lifetime, high quantum efficiency and adjustable emission wavelength. 2+ Ion fluorescence belongs to 3d-3d transition, which has the characteristics of millisecond radiation lifetime and adjustable emission wavelength, so Ce 3+ and Mn 2+ Doped Mg3Al3Si4PO 18 Fluorescent materials have a theoretical basis in multiple anti-counterfeiting applications. 18 With more suitable Mg 2+ Coordination environment, Ce 3+ It emits blue-violet light in the matrix lattice, and the emission peak maximum is about 366nm; Mn 2+ It emits green or red light, with emission peak maxima at approximately 517 and 600 nm. 3+ and Mn 2+ Doped Mg3Al3Si4PO 18 Under different doping concentrations and excitation wavelengths, the fluorescence color of the material changes from orange-red to blue-violet, and the light color changes are obvious. 3+ and Mn 2+ The lowest 5d and 3d energy levels of Mg3Al3Si4PO 18 The energy barrier of the substrate conduction band bottom is different, Ce 3+ and Mn 2+ The thermal stability of fluorescence is different. 3+ The emission band of Mn 2+The absorption bands of Ce are well matched in energy, so 3+ and Mn 2+ Fluorescence has thermal coupling factors, showing a fluorescence process that responds sensitively to temperature changes. Finally, after optimizing the appropriate doping concentration and excitation wavelength, Ce 3+ and Mn 2+ Doped Mg3Al3Si4PO 18 Mn of the material 2+ About Ce 3+ The fluorescence intensity ratio changes with temperature, showing sensitive changes; as the temperature rises, the fluorescence color changes from orange-red light to sky blue light. 3+ and Mn 2+ New ion-activated Mg3Al3Si4PO 18 Fluorescent materials have multiple anti-counterfeiting applications.

[0016] Another aspect of the present invention also provides a method for preparing the above fluorescent material, comprising the following steps:

[0017] S1. According to the chemical composition formula, magnesium salt, silicon dioxide, aluminum oxide, cerium dioxide, manganese carbonate and ammonium dihydrogen phosphate are mixed in an agate mortar to obtain a mixture, and then anhydrous ethanol is added to grind and mix evenly, and then dried at room temperature of about 25° C. for use;

[0018] S2, transferring the dried mixture in S1 to a crucible, calcining it in a reducing atmosphere, and then cooling it to obtain the fluorescent material.

[0019] Preferably, in step S1, the magnesium salt is magnesium oxide or basic magnesium carbonate.

[0020] Preferably, in step S2, the reducing atmosphere is carbon monoxide generated by hot charcoal.

[0021] Preferably, the specific process of the calcination treatment is: heating from room temperature to 1200° C. at a heating rate of 5° C. / min, and then calcining at 1200° C. for 5 hours, and the obtained fluorescent material has good crystallinity and dispersibility.

[0022] The third aspect of the present invention also provides the application of the above fluorescent material in the fields of optical temperature measurement and multiple anti-counterfeiting.

[0023] Specifically, an anti-counterfeiting ink pad is provided, comprising the above-mentioned fluorescent material.

[0024] Preferably, the anti-counterfeiting ink pad also includes polydimethylsiloxane. The polymer is preferably polydimethylsiloxane, which has the advantages of better flexibility and weaker light absorption in the excitation emission range of the luminescent material, and the anti-counterfeiting ink pad can be stored for a short time without a curing agent.

[0025] Further preferably, the fluorescent material passes through a 300-mesh sieve to ensure the fine texture of the ink pad; and the volume ratio of the fluorescent material to polydimethylsiloxane is 3:2, at which time the ink pad has a better consistency.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] (1) The fluorescent material of the present invention has a wide range of excitation and emission wavelengths and exhibits rich fluorescent colors at different doping concentrations, excitation wavelengths and temperatures. 2+ Ion fluorescence mainly originates from the dd transition of electrons, and the fluorescence lifetime is often in the order of milliseconds. 3+ Compared with the existing anti-counterfeiting materials based on ff transition or dd transition activated ions, the ions have higher fluorescence quantum efficiency, nanosecond fluorescence lifetime and adjustable fluorescence color, and can better sensitize Mn 2+ Ion fluorescence, the fluorescent material of the present invention has a wide range of excitation and emission wavelengths and adjustable luminescent colors under different doping concentrations, excitation wavelengths and temperatures, and is expected to further encrypt anti-counterfeiting information through pulse light excitation and decay time conditions, and can be used in optical temperature measurement and multiple anti-counterfeiting fields.

[0028] (2) The preparation method of the fluorescent material of the present invention is a high-temperature solid phase method, the raw materials are easily available, the preparation method is simple, and it is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Mg in the embodiments and comparative examples 3-x-y Ce x Mn y Al 3+x Si 4-x PO 18 X-ray powder diffraction pattern of luminescent materials;

[0030] Figure 2 Ce of Comparative Example 2 3+ Doped Mg3Al3Si4PO 18 Excitation emission spectra of materials and their fitting results;

[0031] Figure 3 Mn of Comparative Example 3 2+ Doped Mg3Al3Si4PO 18 Excitation (a) and emission (b) spectra of the material.

[0032] Figure 4 Mg of Examples 1 to 6 2.97 Ce 0.03 Mn y Al 3.03 Si 3.97PO 18 (y=0.07-0.17) Emission spectrum of the material and the physical image and CIE image when y=0.11 under 365nm excitation;

[0033] Figure 5 The temperature-dependent emission spectrum of the fluorescent material of Example 1 and its physical image and CIE image at different temperatures;

[0034] Figure 6 The anti-counterfeiting ink pad preparation process and anti-counterfeiting pattern of Example 7;

[0035] Figure 7 Schematic diagram of multiple anti-counterfeiting applications of fluorescent materials in Example 1 and a diagram of actual application scenarios. DETAILED DESCRIPTION

[0036] The following examples are further listed to illustrate the present invention in detail. It should also be understood that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the principles described in the present invention belong to the scope of protection of the present invention. The specific process parameters and the like in the following examples are also only examples within a suitable range, that is, those skilled in the art can make a selection within a suitable range through the description herein, and are not limited to the specific data exemplified below.

[0037] The reagents used in the following examples, unless otherwise specified, are all commercially available; the methods used in the following examples, unless otherwise specified, are all achievable by conventional methods.

[0038] Comparative Example 1

[0039] Mg3Al3Si4PO 18 The preparation of the (x=0, y=0) matrix comprises the following steps:

[0040] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1814 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2) and 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 min, mix well and put them into a corundum crucible after drying, and place it in a box furnace, gradually heat it from room temperature to 1200°C over 300 min, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0041] Comparative Example 2

[0042] Mg 1.97 Ce 0.03 Al4Si5PO18 The preparation of the material (x=0.03, y=0) includes the following steps:

[0043] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1814 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4] and 0.0077 g of cerium oxide (CeO2), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and put them into a corundum crucible after drying, and place them in a box furnace, gradually heat from room temperature to 1200°C over 300 minutes, roast in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0044] Comparative Example 3

[0045] Mg 1.93 Mn 0.07 Al4Si5PO 18 The preparation of the material (x=0, y=0.07) includes the following steps:

[0046] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1771 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4] and 0.0121 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C over 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), and continue roasting at a constant temperature for 5 hours. Then the sample is placed in the furnace to naturally cool and anneal to room temperature, and the sample is taken out and ground to obtain the product.

[0047] Example 1

[0048] Mg 1.90 Ce 0.03 Mn 0.07 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.07) material includes the following steps:

[0049] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1771 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0121 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C in 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0050] Example 2

[0051] Mg 1.88 Ce 0.03 Mn 0.09 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.09) material includes the following steps:

[0052] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1759 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0155 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 min, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C over 300 min, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0053] Example 3

[0054] Mg 1.86 Ce 0.03 Mn 0.11 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.11) material includes the following steps:

[0055] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1747 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0190 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C in 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0056] Example 4

[0057] Mg 1.84 Ce 0.03 Mn 0.13 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.13) material includes the following steps:

[0058] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1735 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0224 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C in 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0059] Example 5

[0060] Mg 1.82 Ce 0.03 Mn 0.15 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.15) material includes the following steps:

[0061] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1723 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0259 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C in 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0062] Example 6

[0063] Mg 1.80 Ce 0.03 Mn 0.17 Al 3.03 Si 3.97 PO 18 The preparation of (x=0.03, y=0.17) material includes the following steps:

[0064] Weigh 0.4588 g of aluminum oxide (Al2O3), 0.1711 g of magnesium oxide (MgO), 0.3605 g of silicon dioxide (SiO2), 0.1725 g of ammonium dihydrogen phosphate [(NH)4H2PO4], 0.0077 g of cerium oxide (CeO2) and 0.0293 g of manganese carbonate (MnCO3), put them in an agate mortar, add 5 to 10 mL of anhydrous ethanol, grind for 20 minutes, mix well and dry, then put them into a corundum crucible, and place it in a box furnace, gradually heat it from room temperature to 1200°C in 300 minutes, roast it in a hot carbon reducing atmosphere (carbon monoxide), continue roasting at a constant temperature for 5 hours, then place the sample in the furnace to naturally cool and anneal to room temperature, take out the sample and grind it to obtain the product.

[0065] Example 7

[0066] The Mg obtained in Example 1 1.90 Ce 0.03 Mn 0.07 Al 3.03 Si 3.97 PO 18 The (x=0.03, y=0.07) material was passed through a 300-mesh sieve and then mixed evenly with polydimethylsiloxane (PDMS) at a volume ratio of about 3:2 to obtain an anti-counterfeiting ink pad. The preparation process and anti-counterfeiting pattern are shown in FIG. Figure 6 shown.

[0067] Test experiment

[0068] 1. The samples obtained in the above examples and comparative examples were subjected to phase and performance testing using the following relevant characterization methods:

[0069] (1) X-ray powder diffraction (XRD)

[0070] The phase purity of the samples was collected on a Rigaku D-MAX 2200VPC X-ray diffractometer with a Cu Kα radiation at 40 kV and 26 mA.

[0071] (2) Fluorescence spectrum at room temperature

[0072] The excitation and emission spectra were collected on a Horiba Fluoromax-4 fluorescence spectrometer. A 150W xenon lamp was used as the excitation fluorescence source. The emission spectrum from 330 to 750 nm was divided into two tests and then merged into one emission spectrum based on the transmittance correction of the filter.

[0073] (3) Temperature-dependent fluorescence spectroscopy

[0074] The variable temperature emission spectra from 300 to 550 K were collected in an Edinburgh FS5 fluorescence spectrometer, and a 300 W xenon lamp was used as the fluorescence source.

[0075] (4) Photographing of real objects

[0076] The excited fluorescence of the samples was obtained by using a xenon lamp or a portable UV lamp of an Edinburgh FS5 spectrometer at different temperatures.

[0077] 2. The test results are as follows:

[0078] Figure 1 Mg in the examples and comparative examples 3-x-y Ce x Mn y Al 3+x Si 4-x PO 18 The XRD spectrum of the material corresponds to the standard card PDF12-0303, indicating that the fluorescent material Mg3Al3Si4PO 18 :Ce 3+ , Mn 2+ and its matrix belong to the mineral cordierite structure material; a few XRD miscellaneous peaks correspond to the standard cards PDF 10-0173 and 50-1432, indicating that the sample fluorescent material contains a small amount of unreacted Al2O3 and SiO2 raw materials.

[0079] Figure 2 Ce can be observed 3+ Doped Mg3Al3Si4PO 18 Materials at wave number 18000-30000cm-1 There are two characteristic peaks between them, at a wave number of 27901cm -1 It is characteristic peak 1, with the strongest intensity and a wave number of 26085cm -1 are characteristic peaks 2, respectively derived from Ce 3+ When an ion occupies a Mg site 5 d1- 2 F 5 / 2 and 5 d1- 2 F 7 / 2 Transition fluorescence. In addition, Ce 3+ The strongest absorption of ions is at 300-340nm.

[0080] Figure 3 Mn can be observed 2+ Doped Mg3Al3Si4PO 18 The material has two emission peaks in the range of 490-700nm, with the peak extremes at 517 and 600nm, both from Mn 2+ The 3d-3d transition fluorescence of Mn has the energy levels corresponding to the excitation peaks marked in the figure. 2+ The 517 and 600 nm emission peaks are derived from Mn 2+ Occupies 4 and 6 coordinated Al 3+ and Mg 2+ The fluorescence spectrum obtained by monitoring the emission peak at 680nm contains two Mn 2+ The excitation peak of the luminescence center. In addition, Mn 2+ The strongest absorption of ions is 400-500nm.

[0081] Figure 4 is the normalized emission spectrum of the materials in Examples 1 to 6. Under 320nm ultraviolet light excitation, Ce can be observed simultaneously. 3+ and Mn 2+ With the emission peak of Mn 2+ Doping concentration changes, Ce 3+ and Mn 2+ The emission peak intensity ratio of Mn 2+ The relationship between the total fluorescence intensity and the doping concentration shows that the better Mn 2+ The doping concentration is about 0.09. Under 365nm excitation, Mn 2+ ions, so the material presents Mn 2+ Ion fluorescence. When y=0.11, the actual image and color coordinate (CIE) diagram show that the fluorescent material is yellow. Therefore, adjusting the doping concentration and excitation wavelength can selectively excite Ce. 3+ and Mn 2+ ions to obtain different fluorescent colors.

[0082] Figure 5 (a) is the normalized temperature-dependent emission spectrum of the material in Example 1, taking Mn 2+ Total fluorescence intensity and Ce 3+ The total fluorescence intensity ratio (FIR) is plotted against temperature; and the relationship between the FIR value and temperature is derived and fitted, as shown in Figure 5 (a) Internal. Mn 2+ / Ce 3+ The fluorescence intensity ratio has a better temperature response, the color coordinate change and the actual fluorescence are shown in Figure 5 (b) in.

[0083] Figure 6 This is the process of making the anti-counterfeiting ink pad and its anti-counterfeiting pattern of Example 7. After the obtained fluorescent material is mixed with polydimethylsiloxane, it can remain in the ink pad state for a long time and can be stamped on objects such as glass, ceramics and ironware. At the same time, after stamping the ink pad, spraying a curing agent can obtain an anti-counterfeiting pattern film. The anti-counterfeiting pattern in the film is transparent, and the anti-counterfeiting pattern can only be observed when excited by ultraviolet light or blue light. The figure shows 254nm ultraviolet light excitation, and the orange-red pattern in the glass and film can be seen.

[0084] Figure 7 It is Mg3Al3Si4PO in the embodiment of the present invention. 18 :Ce 3+ , Mn 2+ Schematic diagram of fluorescent material multiple anti-counterfeiting technology. When the excitation wavelength is changed to 254, 365, 417 and 427nm, the stamp pattern of the anti-counterfeiting ink can present rose red, yellow, green and orange red, with rich colors. In addition, the color of the stamp pattern is different at different temperatures. Therefore, the anti-counterfeiting pattern can be multi-encrypted by conditions such as component ratio, excitation wavelength and temperature.

[0085] In summary, the Ce of the embodiment of the present invention 3+ and Mn 2+ Doped Mg3Al3Si4PO 18 The fluorescent material has the structure of the mineral cordierite, and has fluorescent characteristics such as a wide range of excitation and emission wavelengths, strong fluorescence intensity, adjustable fluorescence color, and better temperature response, which can encrypt important information such as patterns or QR codes. The anti-counterfeiting ink prepared based on this material can be attached to materials such as glass, ironware, and polymer films, and encrypt information through light excitation of specific wavelengths and temperature. Compared with most current anti-counterfeiting materials, it has important significance in the field of multiple anti-counterfeiting.

[0086] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0087] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A cerium- and manganese-doped aluminosilicate fluorescent material, characterized in that: The chemical composition formula of the fluorescent material is: Mg 3-x-y Ce x Mn y Al 3+x Si 4-x PO 18 , where x is Ce 3+ The doping concentration of Mn is 0.02≤x≤0.04, and y is Mn 2+ The doping concentration has a numerical range of 0.03≤y≤0.17, the excitation wavelength range of the fluorescent material is 250-500nm, which is a band absorption, and the emission wavelength range is 317-750nm, which is a band emission.

2. The fluorescent material according to claim 1, characterized in that The fluorescent material has adjustable fluorescent colors under different doping concentrations, excitation wavelengths and temperatures, specifically: When the x value is fixed and the y value changes from large to small, the fluorescent color of the fluorescent material changes from orange-red to sky blue; When the values ​​of x and y are constant, the excitation wavelength is changed, and the fluorescent color of the fluorescent material changes within the range of sky blue, emerald green and orange-red; When the values ​​of x and y and the excitation wavelength are fixed, as the temperature changes from low to high from normal temperature, the adjustable fluorescence color range of the fluorescent material is from orange-red to sky blue.

3. The fluorescent material according to claim 2, characterized in that When x=0.03, the y value changes from large to small, and the fluorescent color of the fluorescent material changes from orange-red to sky blue; When x=0.03, y=0.03, and the excitation wavelengths are 254, 320, 417, and 427 nm, respectively, the fluorescent colors of the fluorescent material are rose red, orange red, emerald green, and yellow, respectively; When x=0.03, 0.03≤y≤0.17 and is a constant value, and the excitation wavelength is 300-330nm and is a constant value, within the range of 50-200°C, as the temperature changes from low to high, the adjustable fluorescence color range of the fluorescent material is from orange-red to sky blue.

4. The fluorescent material according to claim 3, characterized in that x=0.03, y=0.07, and the excitation wavelength is 310 nm.

5. A method for preparing the fluorescent material according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1. According to the chemical composition formula, magnesium salt, silicon dioxide, aluminum oxide, cerium dioxide, manganese carbonate and ammonium dihydrogen phosphate are mixed in an agate mortar to obtain a mixture, and then anhydrous ethanol is added to grind and mix evenly, and then dried at room temperature of about 25° C. for use; S2, transferring the dried mixture in S1 to a crucible, calcining it in a reducing atmosphere, and then cooling it to obtain the fluorescent material.

6. The preparation method according to claim 5, characterized in that: The specific process of the calcination treatment is: heating from room temperature to 1200° C. at a heating rate of 5° C. / min, and then calcining at 1200° C. for 5 hours.

7. Use of the fluorescent material according to any one of claims 1 to 4 or the fluorescent material obtained by the preparation method according to any one of claims 5 to 6 in the fields of optical temperature measurement and multiple anti-counterfeiting.

8. An anti-counterfeiting ink pad, comprising the fluorescent material as described in any one of claims 1 to 4 or the fluorescent material obtained by the preparation method as described in any one of claims 5 to 6.

9. The anti-counterfeiting ink pad according to claim 8, characterized in that: The anti-counterfeiting ink pad also includes polydimethylsiloxane.

10. The anti-counterfeiting ink pad according to claim 9, characterized in that: The fluorescent material passes through a 300-mesh sieve, and the volume ratio of the fluorescent material to polydimethylsiloxane is 3:2.

Citation Information

Patent Citations

  • Cipher-loaded multiple colour-match efficient luminous anticounterfeit ink paste, and its preparation and use

    CN100482751C

  • Synthesis method of phosphosilicate white light emission fluorescent powder

    CN110791291A